PENGUATAN SIKAP BERAGAMA PADA UMATBUDDHA MAITREYA DI KAMPUNG PENYENGAT KABUPATEN SIAK PROVINSI RIAU - Megianto Megianto; Rida Jelita; Eko Wahyono Tikno (Jurnal Maitreyawira, 2025)
Strengthening religious attitudes in human life is very important to implement, religion teaches its people to always be able to establish harmony and a high sense of tolerance. This is an obligation and a shared task that must be done and carried out for all levels of society wherever they are. The main thing that must be done by individuals and groups in an area to maintain and carry out their duties in organizing harmonious religious attitudes, namely from each individual must have a loving heart and awareness in ourselves that we as individuals who believe in God must have feelings and feelings that can appreciate every other individual. Attitude and character have a great influence on strengthening religious attitudes, strong faith and deep belief in religious teachings are also true religious attitudes. The purpose of this study was to determine efforts to implement strengthening religious attitudes of Buddhists in Penyengat Village. This study uses a descriptive qualitative research method. Qualitative methods are research methods used to research natural object conditions. The subjects of the study were Buddhist religious figures and community leaders in Penyengat Village. Data analysis was carried out using an interactive model, namely, data reduction, data display, and conclusion drawing/verifications. Based on the results of the study, it can be concluded that: The efforts made by the Maitreya Buddhist community of Penyengat Village, Siak Regency in strengthening religious attitudes have been good, the implementation and real practices have been seen in the daily lives of Maitreya Buddhists in Penyengat Village. The correct religious attitude is that every community in a place can have good moral values, this can be seen in the Penyengat Village area which has and has implemented a sense of belief in the teachings of Maitreya Buddhism by diligently coming to worship and participating in positive activities held at the monastery, being active and carrying out various positive activities at the place of worship or monastery of Maitreya Buddhists in Penyengat Village.